Efficient transient thermal analysis based on spectral element time domain method with curvilinear hexahedrons. (23rd September 2020) - Xue, Yilun; Mi, Jiamei; Wen, Pengfei; Ren, Qiang; Zhou, Yuanguo
Abstract: In this paper, a three‐dimensional transient thermal simulation algorithm based on spectral element method is proposed. This algorithm uses distorted hexahedron for mesh generation, which not only keeps the high efficiency of hexahedron element calculation, but also improves the flexibility of mesh generation. It supports efficient forward difference and unconditionally stable backward difference in time step. Through practical examples and comparison with commercial software, the reliability and stability of the algorithm are verified, and it has obvious advantages in memory consumption and computing efficiency.